Case Report: Neurogenic Thoracic Outlet Syndrome Without Electrophysiologic Abnormality - Kim, Sun Woong; Sung, Duk Hyun (Frontiers in Neurology, 2021)
Neurogenic thoracic outlet syndrome (N-TOS) is a chronic compressive brachial plexopathy that involves the C8, T1 roots, and/or lower trunk. Medial antebrachial cutaneous (MABC) nerve conduction study (NCS) abnormality is reportedly one of the most sensitive findings among the features of N-TOS. The aim of the present study was to report clinical features, imaging findings, treatment, and prognoses of two N-TOS patients with no abnormalities in electrophysiological studies. Both patients presented with paresthesia of unilateral arm, and examination revealed no neurologic deficits. Electrophysiologic studies including MABC NCS were normal. Computed tomography (CT) angiography and brachial plexus magnetic resonance imaging (MRI) of the patients showed compression and displacement of the neurovascular bundle in the thoracic outlet by causative structures. Due to their sensory symptoms and CT angiography and brachial plexus MRI findings, after excluding other diseases, we diagnosed them with N-TOS. With the development of imaging techniques, more patients presenting with clinical features of lower trunk brachial plexopathy and anomalous structures compressing the neurovascular bundle on imaging studies can be diagnosed with N-TOS, even if electrophysiologic studies including MABC NCS do not show abnormalities.